Identification and Expression Analysis of Odorant-Binding and Chemosensory Protein Genes in Virus Vector Nephotettix cincticeps - Xuefei Chang; Yaluan Bi; Haipeng Chi; Qi Fang; Zhaozhi Lu; Fang Wang; Gongyin Ye (Insects, 2022)
The insect odorant binding proteins (OBPs) and chemosensory proteins (CSPs) are involved in the perception and discrimination of insects to host odor cues. Nephotettix cincticeps, one of the destructive pests of rice plants, not only directly damages hosts by sucking, but also indirectly transmits plant viruses in the field. Previous study found that two rice volatiles ((E)-β-caryophyllene and 2-heptanol) induced by rice dwarf virus (RDV) mediated the olfactory behavior of N. cincticeps, which may promote virus dispersal. However, the OBPs and CSPs in N. cincticeps are still unknown. In this study, to identify the OBP and CSP genes in N. cincticeps, transcriptomic analyses were performed. In total, 46,623 unigenes were obtained. Twenty putative OBP and 13 CSP genes were discovered and identified. Phylogenetic analyses revealed that five putative OBPs belonged to the plus-C OBP family, and the other classic OBPs and CSPs were distributed among other orthologous groups. A total of 12 OBP and 10 CSP genes were detected, and nine OBP and three CSP genes were highly expressed in N. cincticeps antennae compared with other tissues. This study, for the first time, provides a valuable resource to well understand the molecular mechanism of N. cincticeps in the perception and discrimination of the two volatiles induced by RDV infection.